Investigação de perdas produtivas e proposta de melhorias em uma indústria de biscoitos amanteigados - Dranka, Giovanne Vinicius (2022)
In the current scenario experienced by industries, it is increasingly important to remain competitive, with fierce competition, to understand the production process in a way that allows improvement, reducing production cost without reducing product quality, it becomes essential for the survival and longevity of organizations. This paper aims to investigate the productive losses in the production of a product from a food company. It is relevant to carry out this study since the company is currently in greater demand than it manages to produce, in need to increase the productivity of its process. For this reason, it was decided to study the production process, identifying losses and proposing improvements that would help to upgrade the production process and increase the company’s productivity. The methodology used was based on direct observation of the process in and we seek from now on to understand and classify the productive losses as well as to propose improvements that make it possible to meet the required demand and maximize profits. Based on the research results, lean manufacturing tools were applied só solutions could be elaborated, whose purpose is to reduce the studied production line’s time and costs.